Transient ischemic attack with infarction: a unique syndrome? - Ay H; Koroshetz WJ; Benner T; Vangel MG; Wu O; Schwamm LH; Sorensen AG (Annals of Neurology, 2005)
It is debated whether transient symptoms associated with infarction (TSI) are best considered a minor ischemic stroke, a subtype of transient ischemic attack (TIA), or a separate ischemic brain syndrome. We studied clinical and imaging features to establish similarities and differences among ischemic stroke, TIA without infarction, and TSI. Eighty-seven consecutive patients with TIA and 74 patients with ischemic stroke were studied. All underwent diffusion-weighted imaging on admission. Symptom duration and infarct volume were determined in each group. Thirty-six patients (41.3%) with TIA had acute infarct(s). Although TIA-related infarcts were smaller than those associated with ischemic stroke (mean, 0.7 vs 27.3 ml; p < 0.001), there was no lesion size threshold that distinguished ischemic stroke from TSI. In contrast, the symptom duration probability density curve was not broad, but instead peaked early with only a few patients having symptoms for longer than 200 minutes. The probability density function for symptom duration was similar between TIA with or without infarction. The in-hospital recurrent ischemic stroke and TIA rate was 19.4% in patients with TSI and 1.3% in those with ischemic stroke. TIA with infarction appears to have unique features separate from TIA without infarction and ischemic stroke. We propose identifying TSI as a separate clinical syndrome with distinct prognostic features.